Gas Tungsten Arc Welding of Dissimilar Material AISI 304, AISI 316 with AISI 4340 – Experimental Investigation for Mechanical Strength and Metallurgical Study - Singla, Sanchit (My University, 2014)
Dissimilar joining of two different metal by welding is the technique to join the two different metals to enhance its mechanical properties as required for some special application. The aim of present study was to investigate the mechanical and metallurgical properties like tensile strength, charpy impact test, microhardness, weld distortion, metallurgical analysis, cracks and dye penetration of dissimilar metal joint stainless steel (AISI 304 & AISI 4340) and (AISI 316 & AISI 4340) during GTAW using the three levels of welding current, shielding gas, gas flow rate, type of filler, pre-heating and post-heating to optimize the process following Taguchi experimental design. Tensile strength of the welded specimens was seen to be dependent on current, filler and post-heating used in various trials in joint of AISI 316 with AISI 4340. Gas type, flow rate and filler are the three influencing parameters which effect the tensile strength of joint AISI 304 and AISI 4340. The maximum tensile strength was seen to be 770 MPa by using current 165 A, gas type Ar + 1.5% He, gas flow rate 12 L/min, filler rod of AISI 304, pre-heating temperature of 175 ºC and post-heating of 650 ºC in joint of AISI 304 with AISI 4340 and 802.40 MPa tensile strength was seen at current 165 A, gas type Ar + 1.5% He, gas flow rate 12 L/min, filler rod of AISI 309, no pre-heating and no post-heating in joint of AISI 316 and AISI 4340. Charpy impact test for toughness results for joint (AISI 304 and AISI 4340) and (AISI 316 and AISI 4340) showed that toughness depends on gas type, filler and post heating. The maximum value of toughness is 147.150 J in case of joint AISI 304 and AISI 4340 and 93.195 J in case of joint AISI 316 and AISI 4340. Dye penetrant test showed that welding was of very good quality and there were negligible amount of defects at corners. Microhardness results for joint AISI 304 and AISI 4340 influenced by current and post-heating having the maximum value of 648.470 and for the joint of AISI 316 and AISI 4340 the maximum value for the micro hardness was found to be 531.00 influenced by gas type, filler rod and post-heating temperature. Weld distortion is found to be minimum of 0.085º in case of joint AISI 304 and AISI 4340 in trial 12 referred from the Table 4.19 and 0.028º in case of joint AISI 316 and AISI 4340 in trial 2 referred from Table 4.22. The surface morphology of the welded plates was characterized by scanning electron microscopy. Microscopy is discussed by considering heat input and flow rate of shielding gas. Dye penetrant test showed that welding was of very good quality. Dye penetration result showed that for both the materials in welded region there is no major flaws and inclusion except a crack observed in a particular sample of dissimilar metal joining of AISI 304 and AISI 316 with AISI 4340.
ME, MED
Keywords: GTAW; Stainless steel; Dissimilar; Mechanical property; Tensile strength; Toughness; Distortion; Microhardness